Analisis Stress Kerja Petugas Air Traffic Controller Terhadap Tingkat Keselamatan Penerbangan di Bandar udara Sultan Muhammad salahuddin Bima, Nusa Tenggara Barat - Nurul Ulfah; Elisabeth Endang Prokosawati (LPPM Institut Nasional Laa Roiba Bogor, 2022)
An air traffic controller (ATC) is one of the jobs with the highest job demands. The safety of the soul is a mental burden that must be borne by each air traffic controller officer. Sultan Muhammad Salahuddin Bima Airport is in charge of providing air traffic guidance services. Guide the pilot from the aircraft's start in the apron, taxi, takeoff, and landing. This study aims to find out if there is work Stresss felt by air traffic controller officers and to gauge the level of flight safety at Sultan Muhammad Salahuddin Bima Airport. This research uses qualitative methods with descriptive qualitative research types. Data collection for this study was conducted at Perum LPPNPI AirNav Indonesia Bima Auxiliary Branch. The study used data from documentation, live observations, and interviews conducted with senior air traffic controllers and junior air traffic controllers. Data analysis techniques use data organizing, data management, data verification and interpretation, and inference. The results of this study showed that there was work stress felt by the air traffic controller officer of Bima Auxiliary Branch. The distance between the Stresss felt in doing the work by the air traffic controller officer is very clearly visible. This is in view of the surrounding environmental conditions that are directly adjacent to the livelihood area of the surrounding population (pond). In addition, Sultan Salahuddin Bima Airport is undergoing reconstruction so that many shocks are felt while inside the tower due to heavy equipment and passing trucks. The results of this study also showed that the level of flight safety at Sultan Muhammad Salahuddin Bima Airport is relatively safe, considering the rare occurrence of accidents and serious incidents. Keywords : air traffic controller, work Stress, flight safety, Sultan Muhammad Salahuddin Bima Airport.